PSYCHOLOGICAL FACTORS OF DEVELOPING SUBJECTIVE WORLD INDEPENDENCE DURING THE STUDENT PERIOD (Multidisciplinary Journal of Science and Technology, 2026)
The article presents an analysis of theoretical views on the psychological factors of developing the independence of the subjective world during the student period. In particular, the concept of the independence of the subjective world in a person, the content of the theoretical views of foreign psychologists in this regard, and the characteristic features are highlighted.